Problems of Normativity, Rules and Rule-Following - Araszkiewicz, M (Springer, 2016)
This book focuses on the problems of rules, rule-following and normativity as discussed within the areas of analytic philosophy, linguistics, logic and legal theory. Divided into four parts, the volume covers topics in general analytic philosophy, analytic legal theory, legal interpretation and argumentation, logic as well as AI& Law area of research. It discusses, inter alia, “Kripkenstein’s” sceptical argument against rule-following and normativity of meaning, the role of neuroscience in explaining the phenomenon of normativity, conventionalism in philosophy of law, normativity of rules of interpretation, some formal approaches towards rules and normativity as well as the problem of defeasibility of rules. The aim of the book is to provide an interdisciplinary approach to an inquiry into the questions concerning rules, rule-following and normativity.